2004
DOI: 10.1111/j.1365-2672.2004.02406.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microwave radiation on Bacillus subtilis spores

Abstract: Aims:To compare the killing efficacy and the effects exerted by microwaves and conventional heating on structural and molecular components of Bacillus subtilis spores. Methods and Results: A microwave waveguide applicator was developed to generate a uniform and measurable distribution of the microwave electric-field amplitude. The applicator enabled the killing efficacy exerted by microwaves on B. subtilis spores to be evaluated in comparison with conventional heating at the same temperature value. The two tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
69
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 22 publications
1
69
1
Order By: Relevance
“…Consequently, microwave radiation is regarded as an alternative method for killing bacteria because of its effectiveness, commercial availability, and lower cost compared with other technologies [Celandroni et al, 2004]. However, the effect of microwave on bacteria depends on food composition and type of microorganism [Castro et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, microwave radiation is regarded as an alternative method for killing bacteria because of its effectiveness, commercial availability, and lower cost compared with other technologies [Celandroni et al, 2004]. However, the effect of microwave on bacteria depends on food composition and type of microorganism [Castro et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…Microwave radiation cannot be thought as simple heating from the inside; the E-fi eld would produce effects on the biological molecules affecting spore structure, different from those attributable only to heat [Celandroni et al, 2004]. Gamma radiation method was used to control this disease, in order to inactivate P. larvae, although signifi cant effect on chemical parameters and enzyme activities of honey were observed [Baggio et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, there has been research demonstrating additional effects, beyond the purely thermal mode of inactivation. For example, distortion of membrane structure and function (Phelan et al, 1994), altered enzyme activity (Dreyfuss and Chipley, 1980), disruption of weak bonds (Betti et al, 2004), increased release of various substances (Woo et al, 2000;Celandroni et al, 2004;Campanha et al, 2007), and increased ionic strength due to an increased current within cells (Watanabe et al, 2000) have all been reported. However, all of the aforementioned research was conducted in the liquid, solid, or aqueous phase.…”
Section: Introductionmentioning
confidence: 99%
“…This latter potential variation could be important, since a spore's DPA content can markedly influence its resistance properties, as noted above, and thus variations in Ca-DPA content might be correlated with heterogeneity in resistance properties of spores in a population. Generally only spore populations' DPA contents have been determined, by boiling or autoclaving large numbers of spores for 15 to 30 min, centrifuging, and measuring the DPA in the supernatant fluid either chemically or by the optical density at 270 nm (4,23,26). Ca-DPA in single spores has been detected using Raman spectroscopy (5,6), but there have not been extensive measurements of Ca-DPA in single spores of various species and strains, as well as in individual spores in a population.…”
mentioning
confidence: 99%